2021
DOI: 10.1111/dmcn.14943
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam as the first‐line treatment for neonatal seizures: a systematic review and meta‐analysis

Abstract: Aim To assess the effectiveness and safety of levetiracetam when used as first‐line treatment of neonatal seizures. Method Four electronic databases, Medline, Embase, Web of Science, and ClinicalTrials.gov were systematically searched from inception until 20th November 2020. Randomized controlled trials (RCTs) and observational studies that included neonates born preterm and term were eligible for inclusion. The primary outcome measure was levetiracetam effectiveness, defined as seizure cessation within 24 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
(162 reference statements)
3
12
0
Order By: Relevance
“…Our results were consistent with another study ( 45 ). That study evaluated the efficacy of LEV vs. PB and found that there was low quality evidence suggesting that LEV might not be more effective than PB.…”
Section: Discussionsupporting
confidence: 94%
“…Our results were consistent with another study ( 45 ). That study evaluated the efficacy of LEV vs. PB and found that there was low quality evidence suggesting that LEV might not be more effective than PB.…”
Section: Discussionsupporting
confidence: 94%
“…Four additional systematic reviews reviewed first-line treatment with phenobarbital and/or levetiracetam, but without consensus-based guidelines. [95][96][97][98] In line with previous guidelines, phenobarbital is recommended as first-line ASM but now with better evidence. Phenobarbital should be used for the shortest duration possible with early discontinuation for neonates with acute provoked seizures responding to treatment.…”
Section: Consensus-based Considerationmentioning
confidence: 65%
“…A systematic review in 2012 summarized pharmacokinetic data for second‐line ASM, and a systematic review in 2013 94 came to similar conclusions as the WHO/ILAE/IBE guideline. Four additional systematic reviews reviewed first‐line treatment with phenobarbital and/or levetiracetam, but without consensus‐based guidelines 95–98 . In line with previous guidelines, phenobarbital is recommended as first‐line ASM but now with better evidence.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Even though PB is the initial drug of choice as first-line treatment of neonatal-onset seizures, 22 some recent systematic reviews concluded that LEV can be used as a first-line antiseizure medication in neonates due to the efficacy, tolerability, and safety profile in neonatal-onset seizures. [23][24][25] Carbamazepine has also been shown to be safe and rapidly effective for the seizures in SLFNE in a previous study. 13 Sodium channel blockers such as carbamazepine and phenytoin are recommended in the treatment of neonatal seizures when a diagnosis of channelopathy is suspected, with a high level of agreement in the latest report from the ILAE (International League Against Epilepsy) task force on neonatal seizures.…”
Section: Discussionmentioning
confidence: 94%